Effects of different incremental treadmill exercise protocols on the autonomic nervous system in healthy college students: a comparative study based on heart rate variability analysis - Cao, Yingying; Li, Shuairan; Zha, Yi; Yan, Xin; Jia, Jingdong; Luo, Yuanyuan; Chi, Aiping (Frontiers in Physiology, 2025)
ObjectivesThis study aimed to examine the acute regulatory effects of three different incremental load treadmill exercise protocols on autonomic nervous system (ANS) function in healthy college students. The ultimate goal was to inform evidence-based training strategies and enhance cardiopulmonary function assessment in this population.MethodsForty healthy male college students were recruited to complete three incremental treadmill protocols: Ellestad A, Ellestad B, and Bruce. Participants were equipped with an energy expenditure monitor (GT9-X, ActiLife 1.0), and heart rate (HR) and heart rate variability (HRV) data were recorded at three time points: pre-exercise, immediately post-exercise, and 5 minutes post-exercise. HRV was analyzed using time-domain indices (SDNN, RMSSD, PNN50), frequency-domain indices (LF, HF), and nonlinear metrics derived from Poincaré plots (SD1, SD2), in order to evaluate the impact of exercise intensity on autonomic regulation.ResultsAll three protocols resulted in significant reductions in time-domain, frequency-domain, and nonlinear HRV indices compared to pre-exercise baseline values (p < 0.01), indicating marked autonomic suppression. Compared to the immediate post-exercise period, HRV continued to decline following the Ellestad A and B protocols (p < 0.01), while a significant rebound was observed after the Bruce protocol (p < 0.01). Furthermore, the LF/HF ratio progressively increased across the three protocols, revealing a significant main effect of exercise intensity (p < 0.01).Conclusion(1) All three incremental treadmill protocols elicited acute HRV alterations, characterized by parasympathetic withdrawal and sympathetic activation, reflecting a transient state of autonomic imbalance; (2) HRV serves as a sensitive physiological marker for detecting exercise-induced fatigue and quantifying training load intensity. Under the Ellestad A and B protocols, heart rate variability (HRV) exhibited a sustained decline throughout the 5-min recovery period, potentially indicating that exercise-induced fatigue load may not have been fully resolved. However, this interpretation warrants further validation through additional objective physiological markers. While the rebound observed after the Bruce protocol may suggest acute autonomic recovery associated with supercompensation and adaptive responses to high-intensity exercise.